Association of Somatic KRAS Variants with Osteolysis in Arteriovenous Malformations - San Basilio, María; Rodríguez-Laguna, Lara; Triana Junco, Paloma; Martínez-Glez, Víctor; Ramirez-Amoros, Carla; Delgado-Miguel, Carlos; Rodriguez-Arias, Juan P.; Lopez-Gutierrez, Juan C. (European Journal of Pediatric Surgery, 2025)
The genetic study of vascular anomalies provides a better understanding of their etiopathogenesis and allows the use of targeted therapies. Activating KRAS pathogenic variants promote cell proliferation by activating MAPK and PI3K signalling pathways, which have been associated with the pathogenesis of vascular anomalies, especially high-flow ones such as arteriovenous malformations (AVMs). AVMs' genomic landscape is extensive, and a genotype–phenotype correlation has not been shown. In this study, we aimed to prove an association between KRAS gene mutations and the presence of osteolysis in patients with AVMs. Herein, we present a clinical–molecular retrospective study of patients with AVMs, bone involvement, and KRAS pathogenic variants.A retrospective review of patients with AVMs and KRAS somatic variants followed by the Vascular Anomalies Unit at our institution was performed. All patients present bone involvement. We analyzed demographics, clinical features (AVMs location, phenotype), treatment received, and response to treatment. Previous imaging studies were used to assess bone involvement. Genetic studies were performed by high-throughput sequencing using a custom-designed panel.Of the 77 patients with AVMs currently followed in our clinic, 60 (77.9%) had genetic testing, and 19 (31.6%) presented a KRAS somatic activating variant and were therefore included in the study. There were 12 women and 7 men aged 10 to 79 years. When studying radiographies or CT scans, we found that all 19 patients associated osteolysis adjacent to the AVMs. Regarding the KRAS variants, the most frequent one was p.Gly12Asp, followed by p.Gln61His and p.Gly13Arg. Additionally, we reviewed imaging studies from the other 41 patients with AVMs and different pathogenic variants such as MAP2K1, RASA1, and BRAF, and did not find osteolysis.We have described for the first time the relationship between somatic, activating KRAS pathogenic variants and osteolysis in patients with AVMs. Early detection of these KRAS alterations in this type of patient should lead us to rule out bone involvement. Moreover, identifying these mutations may help guide targeted therapies, potentially preventing the development of osteolysis and improving patient outcomes.
Keywords: arteriovenous malformation; KRAS; osteolysis